Implementation of the Value Management of The Benefit of The People's Endowment Fund Through The BPKH Benefit Program (Case Study of BPKH Benefit Partners - BAZNAS RI) - Efri Andini; Nur Fatwa (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2024)
The Hajj Financial Management Agency (BPKH) is a public legal entity established under the mandate of Law Number 34 of 2014 concerning the financial management of Hajj. One of the objectives of the financial management of Hajj is to increase the benefits for the benefit of Muslims through benefit programs. The BPKH benefit program is funded by the benefit value of the People's Endowment Fund and is a social assistance activity as well as the company's Corporate Social Responsibility (CSR), in accordance with the provisions of the law. Construction of religious facilities and infrastructure. The BPKH benefit program is a new thing that comes as another form of company's Corporate Social Responsibility (CSR). The purpose of this research is to conduct a literature study and a comparison on the management of the value of the benefits of the community endowment through the bpkh benefit program (a case study of the benefit partners of BPKH - BAZNAS RI). Social services to reduce poverty and ignorance in the country through education and da'wah activities as well as economic empowerment of the people. Therefore, the role of managing the value of the Ummah Endowment Fund which is transparent, sharia and accountable is indispensable.